Antimicrobial use and factors influencing prescribing in medical wards of a tertiary care hospital in Malaysia - Akter, Seikh Farid Uddin; Abdul Rani, Mohammed Fauzi; Ab Rahman, Jamalludin; Nordin, Mohamad Sahari; Satwi, Sapari; Awang, Mohamed; Rathor, Mohammad Yousuf; Md Aris, Mohd Aznan (International Journal of Science, Environment and Technology, 2012)
Abstract: To ascertain the pattern of antimicrobial use and to analyze the selected core drug use indicators – prescribing indicators – a prospective study was conducted in 2008 in medical wards of a tertiary care hospital in Malaysia. Every patient in the medical wards of the selected hospital who was being treated with antimicrobial(s) during the data collection period was considered a potential study subject for this study. The treatment charts of 209 admitted patients were reviewed. Pneumonia was the leading diseases among them (26.3%). The most commonly used antimicrobials were amoxicillin with clavulanate (augmentin), erythromycin, cefuroxime, ceftriaxone and ampicillin sodium with sulbactam sodium (unasyn). The level of generic prescribing of antimicrobials was just above the half of all prescribed courses (54.3%) and the intravenous route was the preferred method of administration (57.3%). The mean number antimicrobials received by the studied patients were 1.8 (± 0.9). The majority of them (53.6%) received two or more antimicrobials for their treatments. The evident of high percentages of patients received antimicrobial treatment in combinations reflected the potential of higher proportion of inappropriate treatment of different diseases and suggested the ample scope for intervention to improve antimicrobial use in the hospital.